EMPOWERING DIGITAL TRANSFORMATION IN EDUCATIONAL MANAGEMENT: A COMMUNITY SERVICE PROGRAM AT UNISSA, BRUNEI DARUSSALAM - Fitriadi, Ahmad; Mulawarman, Widyatmike Gede; Azainil, Azainil; Warman, Warman; Susilo, Susilo (LPPM Univ. Ibn Khaldun Bogor, 2025)
The rapid advancement of digital technologies has fundamentally reshaped educational systems worldwide, compelling higher education institutions to adopt adaptive management strategies that align with evolving pedagogical and operational demands. In this context, a community service program (Pengabdian kepada Masyarakat – PKM) was implemented at Universiti Islam Sultan Sharif Ali (UNISSA), Brunei Darussalam, to strengthen institutional capacity for digital transformation in educational management. The program specifically targeted UNISSA’s administrators, lecturers, IT personnel, and selected student representatives, fostering a comprehensive understanding of digital governance, smart campus systems, Learning Management System (LMS) optimization, and the integration of artificial intelligence (AI) in higher education. Using a combination of public seminars, interactive workshops, hands-on demonstrations, mentoring sessions, and knowledge-sharing activities, the initiative facilitated bilateral learning between Universitas Mulawarman (UNMUL) and UNISSA. The program’s outcomes included improved comprehension of digital management frameworks, heightened awareness of the role of digital leadership and robust infrastructure, and the identification of strategic pathways for sustaining transformation. Additionally, cross-institutional exchange enriched participants’ perspectives by integrating global best practices with localized policy and cultural contexts. The PKM not only advanced UNISSA’s readiness for digital innovation but also strengthened long-term academic collaboration between Indonesia and Brunei Darussalam.